Chemical Compositions Of Ipomea Aquatica (Green Kangkong) - IGWENYI, I. O.,; OFFOR, C. E.,; AJAH, D. A.,; NWANKWO, O. C.,; UKAOMAH, J. I.,; AJA, P. M., (International Journal of Pharma and Bio Sciences, 2011)
Proximate analysis on Ipomea aquatica (green kangkong) was carried out using standard methods. The results revealed 51.36% moisture, 42.18% carbohydrate, 1.70% protein, 2.75% ash, 1.20% fiber and 0.81% fat. The investigation of mineral content in μg/ml showed that the vegetable was relatively high in iron, magnesium and calcium. Other minerals that were present include phosphate, manganese, sulphate and nitrates. The vitamin content was investigated using spectrophotometric methods and it revealed high contents in mg/100g of vitamins A, B1, C and K. Relatively water-soluble vitamins were predominant over fat-soluble vitamins. Phytochemical screening of green kangkong revealed high concentrations of alkaloids, reducing sugar, soluble carbohydrate, flavonoids, while it contained lower concentrations of steroids, phenols, glycosides, β-carotene, saponins and tannins. The high carbohydrate, vitamin and mineral contents showed that the plant material can be a good source of nutrient for man and animal food. The natural endowments of phytochemicals showed that the plant has serious pharmacological and therapeutic effects apart from its nutritional essence.